Shielding Effect of Boron Carbide Aluminium Metal Matrix Composite against Gamma and Neutron Radiation - Akkas, A.; Tugrul, A. B.; Buyuk, B.; Addemir, A. O.; Marsoglu, M.; Agacan, B. (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In this study, boralyn (boron carbide-aluminum metal matrix composite material Al/B4C) composite materials were investigated on shielding effect against gamma and neutron radiations. The samples were prepared as 5 wt%, 10 wt%, 15 wt%, and 20 wt% reinforcement content and for each content of material has composed in five different average particle sized (3 mu m, 53 mu m, 113 mu m, 200 mu m, and 500 mu m). Linear and mass attenuation coefficients were calculated experimentally for each composite material against Cs-137 gamma source. Theoretical mass attenuation coefficients of material were calculated by using XCOM computer code. Then the theoretical results were compared with experimental results. Then, macroscopic cross-section values were calculated experimentally for each composite material against Pu-Be neutron source. As the conclusion of the study, it could be understood that in spite of decrease of the attenuation coefficient against gamma radiation, the adding materials give rise to increase the shielding ability of material against neutron radiation.
Keywords: BEHAVIOR; Physics